HUBUNGAN SOSIAL EKONOMI ANTARA PEMILIK USAHA BATU BATA DENGAN PEKERJA BATU BATA DI RW 22 KELURAHAN SAIL KECAMATAN TENAYAN RAYA - Debora Yanti Hutajulu; T. Romi Marnelly (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
Industry is one business that created humans by managing natural resources to be something that could be useful to humans themselves. One industry that is made is that the brick industry including small and medium businesses, which include activities that transform basic goods or semi-finished goods or goods of less value to goods of higher value. Brick making has now spread including Indonesia, one of which is the city of Pekanbaru which has several brick industry, for example in RW 22 Sail Village Tenayan Raya Subdistrict which has 98 business owners bricks and 294 workers. Despite having differences, but the community RW 22 Village Sail Tenayan Raya Subdistrict live in harmony, including workers and owners of the bricks that have a concern with each other. if there is grief will come to visit to give comfort, if it held a celebration it would invite each other. The economic relations between the owner and the workers is also good, if they borrow money from the owner then they will make an agreement on the debt payment so there is no dispute.Keywords: business owners of bricks, brick workers, socio-economic relations